COMPARISON OF ZOOPLANKTON DENSITY ESTIMATION USING BONGO PLANKTON NET AND UNDERWATER ACOUSTICS METHOD - Ellis Nurjuliasti Ningsih; Riris Aryawati; Amanda AP Febrianti; Freddy Supriyadi (UNIVERSITAS SRIWIJAYA, 2021)
Zooplankton is one of the factors that can affect water conditions. The existence and abundance of zooplankton can indicate the level of water fertility. Zooplankton abundance can be observed by using two methods. These are the bongo plankton net and underwater acoustics method. This study aims to determine the abundance of zooplankton using bongo plankton net 250 ?m mesh size and underwater acoustics method using Simrad EK15 200 kHz frequency. This study was conducted in July 2019 in the Banyuasin estuary. The results showed the abundance of zooplankton using bongo plankton net ranged from 7-116 ind/m3, and the zooplankton density in underwater acoustics ranges from 0-2700 ind/m3. It means the ratio between both of the methods is around 1:20. The comparison could illustrate the difference in zooplankton density. It is necessary to adjust the specifications instrument and sampling technique of zooplankton sampling equipment and underwater acoustics instruments to obtain more accurate results.Keywords: Abundance, Banyuasin estuary, hydroacoustics, zooplankton,